Financing global development: The role of local currency bond markets in Sub-Saharan Africa - Kathrin Berensmann; Florence Dafe; Nannette Lindenberg; Ulrich Volz (Deutsches Institut für Entwicklungspolitik (DIE), 2015)
The UN Conference on Financing for Development in Addis Ababa in July 2015 will pave the way for the implementation of the post-2015 development agenda. The Briefing Paper series “Financing Global Development” analyses key financial and non-financial means of implementation for the new Sustainable Development Goals (SDGs) and discusses building blocks of a new framework for development finance. The enormous deficiencies in Sub-Saharan Africa's (SSA) local and regional infrastructure in areas such as water, sanitation, transport and energy facilities, mean that long-term financial resources must be mobilised to ensure sustainable development. Local currency bond markets (LCBMs) are still generally underdeveloped in SSA in comparison with other regions of the developing world. Yet for all SSA countries, including the poorest economies, LCBMs could become an important means of long-term financing and reduce the financial vulnerability associated with foreign currency borrowing. LCBMs provide alternative sources of financing and reduce a country's dependency on foreign debt. They allow for risk diversification and can mitigate the effects of external shocks. Local currency government bond markets are also important for benchmarking corporate bond markets – another way to finance companies for the long-term. Policy recommendations for improving LCBM development in SSA We recommend supporting LCBM development through national and regional initiatives that strengthen the institutional and regulatory environments, broaden the investor base and create more liquid secondary markets. Authorities in SSA need to ensure favourable macroeconomic environments and develop suitable financial infrastructures. To avoid financial turbulence, capital account liberalisation should be pursued very carefully, with LCBM development going hand-in-hand with solid financial and institutional development. SSA authorities should put into place appropriate strategies for managing debt and capital accounts in order to address capital in- and out-flows, and ensure trained personnel to implement them. Authorities should further ensure the safety of investments by guaranteeing profit repatriation. In this respect, law enforcement is crucial. Bilateral and multilateral donors can support LCBM development by offering technical assistance to realise debt management strategies. The Debt Management Facility of the World Bank and the IMF and the Debt Management and Financial Analysis System of the United Nations Conference on Trade and Development (UNCTAD) are good examples of donor support for developing countries that provide country-specific technical assistance at different levels. In SSA the African Development Bank has put in place the African Market Initiative (AFMI) which promotes LCBM development in SSA. Another fine example of donor support is the World Bank Group's Global Emerging Markets Local Currency Bond Program (Gemloc), which promotes LCBM development in emerging market economies. Since LCBMs can supply long- or medium-term capital for both governments and companies they have a large potential for financing the infrastructure needed in SSA and for supporting the achievement of the SDGs.
Keywords: 330; Entwicklungsfinanzierung und öffentliche Finanzen; Agenda 2030